BADIIY TARJIMA NAZARIYASIDA QAHRAMON QIYOFASI TUSHUNCHASI TALQINI. - Tursunmuratova Dilnoza Turamuratovna (International Journal of Literature and Language Studies, 2026)
The article analyzes the definitions given by translation scholars to the concept of a literary character — one of the main issues in modern translation theory — as well as its structural components (external portrait, inner world, idiolect, subtext)